2016
DOI: 10.1111/ejh.12789
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein lipase in chronic lymphocytic leukemia: function and prognostic implications

Abstract: Chronic lymphocytic leukemia (CLL) is a clinically heterogeneous disease characterized by the accumulation of a clonal population of B cells in peripheral blood, bone marrow, and lymphoid organs. More than 10 years ago, lipoprotein lipase (LPL) mRNA was identified as being strongly expressed in patients experiencing a more aggressive phenotype, while CLL patients with an indolent disease course lack expression of this marker. Since then, several reports confirmed the capability of LPL to predict CLL disease ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 58 publications
0
11
0
Order By: Relevance
“…Our findings are further strengthened by our observation of higher levels of STAT3 in CLL lymph nodes compared to healthy controls. STAT3 drives the expression of LPL (Rozovski et al, 2015) and whilst measuring the protein levels of LPL in CLL have proven difficult (Porpaczy et al, 2013;Heintel et al, 2005), increased LPL mRNA levels have been documented [reviewed in (Rombout et al, 2016)]. High levels of LPL are strongly correlated with UM-CLL and correlate with an aggressive disease course and poor prognosis (Rosenwald et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are further strengthened by our observation of higher levels of STAT3 in CLL lymph nodes compared to healthy controls. STAT3 drives the expression of LPL (Rozovski et al, 2015) and whilst measuring the protein levels of LPL in CLL have proven difficult (Porpaczy et al, 2013;Heintel et al, 2005), increased LPL mRNA levels have been documented [reviewed in (Rombout et al, 2016)]. High levels of LPL are strongly correlated with UM-CLL and correlate with an aggressive disease course and poor prognosis (Rosenwald et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Provided that CLL cells display HSPGs on their surface [ 62 ] and that LPL forms homodimers, it could occur that a bridging between leukemic B-cells and other cells expressing surface HSPGs or GPIHBP1 such as endothelial cells would be mediated by LPL. Although several groups have already speculated about it, a cell–cell bridging role for LPL in CLL pathogenesis still has to be demonstrated [ 30 , 35 , 63 ]. If such a bridging actually occurred, LPL would be pivoting between surface HSPGs on the B-CLL cell side, and either HSPGs or GPIHBP1 on their counterpart.…”
Section: Lpl In Chronic Lymphocytic Leukemiamentioning
confidence: 99%
“…Rombout et al have found that two SNPs commonly found in LPL , rs328 (premature stop codon) and rs13702 were significantly associated with CLL outcome [ 63 ]. Although both SNPs are well-known gain-of-function mutations [ 64 , 65 ], the authors of the aforementioned study reported not to have been able to detect significant differences in LPL mRNA, protein levels, or enzymatic activity in patients carrying the SNPs [ 63 ]. How these mutations affect clinical outcome in CLL is still unclear, but whether these SNPs might have a role—if any—in LPL non-metabolic functions has not been explored yet.…”
Section: Lpl In Chronic Lymphocytic Leukemiamentioning
confidence: 99%
“…However, emerging evidence indicates that prognosis cannot be restricted to the IGVH mutation status, and great effort is still required for identifying molecular markers of disease progression. The enhanced expression of CD38 , Lipoprotein lipase ( LPL ) and Zeta-chain-associated protein kinase 70 ( ZAP70 ) was associated to U-CLL with rapid fatal outcome 4 7 . Nevertheless, these genes were not proved to be reliable biomarkers for evaluating the clinical course of CLL and the effectiveness of therapy.…”
Section: Introductionmentioning
confidence: 99%